2000
DOI: 10.2307/1565272
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Ecology and Survivorship of Resident and Translocated Hognose Snakes (Heterodon platirhinos)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 21 publications
8
54
1
Order By: Relevance
“…Habitat selection.-Heterodon platirhinos in the park used forested areas that constituted the majority of the area, but also demonstrated strong selection of open habitats relative to their availability, which is consistent with other published studies and natural history observations (Platt 1969;Plummer and Mills 2000;Lagory et al 2009; but see Robson 2011). Goulet et al (2015) describe habitat selection at the home range scale of snakes from the same study area as Lagory et al (2009), and showed non-random selection for Hemlock (Tsuga canadensis) and pine (Pinus sp.)…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Habitat selection.-Heterodon platirhinos in the park used forested areas that constituted the majority of the area, but also demonstrated strong selection of open habitats relative to their availability, which is consistent with other published studies and natural history observations (Platt 1969;Plummer and Mills 2000;Lagory et al 2009; but see Robson 2011). Goulet et al (2015) describe habitat selection at the home range scale of snakes from the same study area as Lagory et al (2009), and showed non-random selection for Hemlock (Tsuga canadensis) and pine (Pinus sp.)…”
Section: Discussionsupporting
confidence: 88%
“…However, we acknowledge that this is may be a function of the small number of snakes tracked. Lagory et al (2009) reported an average MCP of 51.7 ± 14.7 ha, Robson (2011) reported 39.43 ± 6.3 ha, and Plummer and Mills (2000) reported 50.2 ± 6.4 ha, but Buchanan (2012) reported a similar MCP of 31.0 ± 15.6 ha. A subsequent study of home range at the same site as Lagory et al (2009) revealed an even larger home range of 72.7 ± 35.3 ha (n = 5).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Though LDT is likely to remain a popular tool for managing snake populations, and it has been studied in a variety of species (Reinert and Rupert, 1999;Plummer and Mills, 2000;Nowak et al, 2002;Butler et al, 2005;Brown et al, 2008;Roe et al, 2010), studies have largely focused on the effects of LDT on spatial ecology (movements and activity range size) and mortality. Of the aforementioned studies, only Roe et al (2010) incorporated study of physiological impacts of LDT, studying the impact on body temperature in Northern Water Snakes (Nerodia s. sipedon).…”
Section: Catenatus)mentioning
confidence: 99%
“…The mitigation of human-snake conflict through the relocation of nuisance animals has been the primary motivation behind snake translocation (Hardy et al, 2001;Nowak et al, 2002;Butler et al, 2005;Kingsbury and Attum, 2009). However, now that snake declines are being documented (Kingsbury and Attum, 2009), translocation has increasingly been investigated as a purely conservation tool, through the augmentation of a current population to increase its viability or the creation of a new population in a part of a species' historical range (Plummer and Mills, 2000;King et al, 2004;Kingsbury and Attum, 2009;Roe et al, 2010). Since translocation is likely to remain a popular management tool, especially for venomous snakes, it is crucial that its effects on subject animals be further studied.…”
Section: Introductionmentioning
confidence: 99%